Ilokano-English dictionary - Gelade, George P. (CICM Missionaries, 1993)
This dictionary was written with a double purpose: "1. To keep those who, in their ministry, are in need of an Ilokano-English dictionary, and 2. To provide a basis for further research." The dictionary has approximately 18,500 cross references. It is arranged alphabetically; acute accent available and this indicates syllabic stress; there are abbrevations. Words derived from English and other European language, except Spanish, have been left out as a general rule."